2019
DOI: 10.6087/kcse.171
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of “Principles of transparency and best practice in scholarly publishing” in academic society published journals

Abstract: Four international associations, including the Open Access Scholarly Publishers Association, the Directory of Open Access Journals, the Committee on Publication Ethics, and the World Association of Medical Editors declared the third version of "Principles of transparency and best practice in scholarly publishing" to ensure transparency and quality in journal publications. This study is aimed at assessing the guidelines from the journals' websites manually. Methods: In this study, three researchers investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…We found that the 59 Korean academic journals analyzed in this study showed poor compliance with similar aspects of the "Principles of transparency and best practice in scholarly pub-lishing" as we identified in 781 journals worldwide in our study in 2019 [8]. Korean journals showed relatively good compliance in the areas of readership, author fees, Committee on Publication Ethics' guideline, and archiving.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…We found that the 59 Korean academic journals analyzed in this study showed poor compliance with similar aspects of the "Principles of transparency and best practice in scholarly pub-lishing" as we identified in 781 journals worldwide in our study in 2019 [8]. Korean journals showed relatively good compliance in the areas of readership, author fees, Committee on Publication Ethics' guideline, and archiving.…”
Section: Discussionsupporting
confidence: 44%
“…Similarly to a previous article published by the same researchers [8], we classified the 16 principles into four subgroups: basic journal information, publication ethics information, copyright and archiving information, and profit model information. If compliance with a criterion was satisfactory, the item was marked as "yes"; otherwise, it was marked as "no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the editors and editorial board members have played a superb role in these developments. They introduced an internationallevel editorial policy, including careful review, and firmly adhere to international ethical guidelines, including the Principles of Transparency and Best Practice in Scholarly Publishing, 3rd version [13,14].…”
Section: Types and Titles Of Sources Cited By Articles In Ultrasonogrmentioning
confidence: 99%
“…should be clearly marked on the website as necessary bibliographic information associated with the journal. The quickest way to clarify the essential bibliographic information was to evaluate a journal's compliance with the "Principles of transparency and best practice in scholarly publishing, 3rd version" [3]. All journals that apply for KOFST funding can attempt to follow these standards.…”
Section: Generalizabilitymentioning
confidence: 99%